Evaluation of Interventions to Reduce Multiply Controlled Vocal Stereotypy. (July 2015) - Scalzo, Rachel; Henry, Kelsey; Davis, Tonya N.; Amos, Kally; Zoch, Tamara; Turchan, Sarah; Wagner, Tara
This study examined four interventions targeted at decreasing multiply controlled vocal stereotypy for a 12-year-old boy diagnosed with autism spectrum disorder and a severe intellectual disability. These interventions included Noncontingent Music, Differential Reinforcement of Other Behaviors, Self-Recording, and Functional Communication Training (FCT). In addition to measuring vocal stereotypy during each condition, task engagement and challenging behavior were also monitored. Across conditions, vocal stereotypy did not vary significantly from baseline except in FCT, when it decreased significantly. Task engagement was higher in this condition as well. It is hypothesized that FCT provided an enriched environment by increasing social interaction and access to desired items as well as removal of less preferred activities. For these reasons, there was a decrease in the need for the participant to engage in vocal stereotypy and challenging behavior and increase in his ability to engage in a task.